2018
DOI: 10.5194/bg-15-885-2018
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of carbon cycling to long-term nutrient input and altered hydrological conditions in a continental Canadian peatland

Abstract: Abstract. Peatlands play an important role in global carbon cycling, but their responses to long-term anthropogenically changed hydrologic conditions and nutrient infiltration are not well known. While experimental manipulation studies, e.g., fertilization or water table manipulations, exist on the plot scale, only few studies have addressed such factors under in situ conditions. Therefore, an ecological gradient from the center to the periphery of a continental Canadian peatland bordering a eutrophic water re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
(87 reference statements)
1
11
2
Order By: Relevance
“…The relatively positive  13 C value of CO2 (-10.13‰) in the Mollisol relative to C4 litter (-13.3‰) and soil organic C (-22.0‰) may be attributed to a small proportion of CO2 generated by the dissolution of carbonate (-2.08‰). In comparison, the more positive  13 C values of CO2 under the anaerobic phase (-9.05‰ for the for the Oxisol) coincided with higher CH4 percentages, as is commonly observed in consistently saturated wetland systems with much greater CH4 production (Corbett et al, 2013;Berger et al, 2018). Compared with the relatively stable  13 C value of CO2 in the control, the mean  13 C values of CH4 under the anaerobic phase (-43.97‰ for the Mollisol and -49.16‰ for the Oxisol) were consistent with a mixture of hydrogenotrophic and acetoclastic methanogenesis (Blaser and Conrad, 2016).…”
Section: Effects Of Dynamic Redox Environments On  13 C Values Of Chmentioning
confidence: 63%
“…The relatively positive  13 C value of CO2 (-10.13‰) in the Mollisol relative to C4 litter (-13.3‰) and soil organic C (-22.0‰) may be attributed to a small proportion of CO2 generated by the dissolution of carbonate (-2.08‰). In comparison, the more positive  13 C values of CO2 under the anaerobic phase (-9.05‰ for the for the Oxisol) coincided with higher CH4 percentages, as is commonly observed in consistently saturated wetland systems with much greater CH4 production (Corbett et al, 2013;Berger et al, 2018). Compared with the relatively stable  13 C value of CO2 in the control, the mean  13 C values of CH4 under the anaerobic phase (-43.97‰ for the Mollisol and -49.16‰ for the Oxisol) were consistent with a mixture of hydrogenotrophic and acetoclastic methanogenesis (Blaser and Conrad, 2016).…”
Section: Effects Of Dynamic Redox Environments On  13 C Values Of Chmentioning
confidence: 63%
“…Then, slow diffusive transport along the concentration gradient from deep anoxic peat layers to the atmosphere leads to CH 4 release. In upper, unsaturated and oxic peat zones that typically extend only about a few decimetres (Whalen, 2005;Limpens et al, 2008), CH 4 might get consumed by methanotrophic microbes (Chasar et al, 2000;Whalen, 2005;Berger et al, 2018). Consequently, water table position and fluctuations strongly control the amount of emitted CH 4 (Blodau and Moore, 2003;Whalen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…While CH 4 oxidation suppresses CH 4 emissions in diffusion-dominated systems, ebullition by fast release of gas bubbles or plant-mediated transport by aerenchymatic roots can substantially increase CH 4 emissions (Fechner-Levy and Hemond, 1996;Joabsson et al, 1999, and references therein;Chasar et al, 2000;Colmer, 2003;Whalen, 2005;Knoblauch et al, 2015;Burger et al, 2016;Berger et al, 2018). With a high share of ebullitive fluxes, vegetated or open water pools in peatlands are considered to be strong CH 4 emitters (Hamilton et al, 1994;Blodau 2002;Burger et al, 2016) that have, however, received less attention than the vegetated surfaces (Pelletier et al, 2014). Pools can even turn the peatlands' C balance into a source (Pelletier et al, 2014), but examples of low-emission pools have also been reported (Knoblauch et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations